Current Issues in Highway–Rail Grade Crossing Hazard-Ranking and Project Development. Issue 1 (January 2017) - Sperry, Benjamin R.; Naik, Bhaven; Warner, Jeffery E.
This paper reports on a comprehensive research study of hazard-ranking models for prioritization and selection of highway–rail grade crossing improvement projects. The U.S. Department of Transportation (DOT) accident prediction model is the most commonly used hazard-ranking model, although 11 states use state-specific models. Key variables not included in the U.S. DOT model but included in state-specific models may provide useful insight for identifying hazardous crossing locations. Emerging issues, such as the crash modeling approach used by the U.S. DOT model and the application of economic analysis principles in project prioritization, are also discussed. The findings reported in this paper provide a starting point for a broader discussion among all stakeholders in the grade crossing safety community about ways to improve hazard-ranking and project selection for highway–rail grade crossing investments.